Clinical, laboratory and epidemiological aspects of Cryptosporidium parvum and Cryptosporidium hominis infection: a integrative review - R. L. M. Mendonça; M. S. Miranda; A. C. Guimarães; A. P. Queiroga; H. F. M. Câmara; P. H. L. T. S. Anjos; J. V. Ferro; H. B. G. Messias; T. L. G. Q. Maranhão; A. C. S. Omena; A. C. Silva; C. J. Santos Júnior; et al. (Brazilian Journal of Biology)
Abstract Cryptosporidium parvum and Cryptosporidium hominis infection causes cryptosporidiosis, which in humans can result in watery diarrhea that is usually self-limited in immunocompetent individuals, but can be chronic and fatal in immunocompromised individuals. To understand and expose current clinical, laboratory and epidemiological data, as well as characteristics of cryptosporidiosis worldwide. This is a literature review by the integrative review method, qualitative and exploratory through the publications selected in the databases: BVS, ScieLO, MEDLINE and LILACS. Inclusion criteria were: publications from the last 6 years and articles in Portuguese, English and Spanish. Exclusion criteria were: research not evidenced in humans and duplicate articles, as well as articles that were not available in full and free of charge. The variables analyzed were cases by regions of the world, transmission mechanisms and symptoms. In this study, 40 articles were submitted. Regarding transmission, the most commonly reported route was the anthroponotic route, being mentioned in 40% of them (16); the zoonotic route was also prominent, being mentioned in 22.5% (9) of the articles. As for the symptoms, diarrhea was the most present, being mentioned in 82.5% (33 articles), other symptoms mentioned were headache 12.5% (5), joint pain 5% (2) and eye pain 5% (2). With regard to laboratory diagnosis, the most commonly used method was polymerase chain reaction (PCR) 75% (30) and modified Ziehl Neelsen staining 22.5% (9). Therefore, it is noticeable that the main complication of cryptosporidiosis is gastroenteritis, whose manifestations range from diarrhea to abdominal cramps. This parasite is widely distributed throughout the world, mainly in developing and underdeveloped countries, transmitted by the oral-fecal route. In addition, it is notable that PCR was the most commonly used laboratory method for diagnosis, which shows that the disease can be easily detected once the symptoms have manifested themselves. In this sense, knowledge about the parasite is necessary for prevention and thus avoid major complications.